Advances in purine and pyrimidine metabolism in health and diseases. (1st December 2016) - Hirano, Michio; Peters, Godefridus J.
ABSTRACT: In June, 2015, the Purine and Pyrimidine Society organized the 16th biennial symposium on Purine and Pyrimidine metabolism at the Faculty House of Columbia University, New York City. This exciting meeting focused on these important molecules, new developments in inborn errors of metabolism; therapeutic analogs. In addition, the biochemistry of mammalian and non-mammalian systems were discussed. Due to significant advances in molecular medicine, the boundaries between clinical and basic sciences have merged into exciting translational research, of which a small portion was highlighted in the presymposium.